Study of Existing Barn and Animal Hygiene Practices in Milch Cows and Buffaloes in Sabarkantha District (Indian Journal of Animal Production and Management, 2024)
This study aimed to investigate the dairy farming practices and management in Sabarkantha district.  A total of 90 livestock owners were randomly selected from six villages representing the Himatnagar,  Idar, and Prantij talukas, encompassing three farm size categories based on the number of milch  animals: Category A (20  Milch animals). The herd composition analysis revealed that cattle were the primary milch animals in  the studied farms, with an average total herd strength of approximately 20 cattle and 5 buffaloes. The  respondents' personal characteristics indicated a relatively good level of education, with 32% having  attained a graduate level of education. The majority of farmers fell into the 50-65 years age group,  and most had more than 10 years of experience in dairy farming. Analysis of milking and healthcare  practices revealed that a significant number of farmers employed the knuckling method of milking,  which is not recommended. Dry cow therapy and milking parlour usage were less prevalent, but  proper drying periods and vaccination and deworming practices were generally followed. Housing  practices indicated that most farmers used pacca (concrete) floors and provided adequate light and  ventilation. Single-line housing was the most popular system, and drainage facilities were generally  adequate. However, milking hygiene practices were found to be suboptimal, with limited use of teat  dips or antiseptic udder washing. Overall, the study highlights the need for improvement in milking  hygiene practices, along with targeted interventions to enhance dairy management in Sabarkantha  district.
Keywords: Milking hygiene; barn hygiene; mastitis; milking management; buffaloes